Writing DOS device drivers in C - Clovis L., Tondo; Adams, Phillip M. (s/c: Prentice- Hall, Inc, 1990)
Sus temas principales son: introduction, Fundamentals, DOS device drivers fundamentals, A DOS device drivers template, what if it doesn't work?, DOS character device drivers, Disk/ Diskette fundamentals, DOS block device drivers, DOS device drivers test methodology, DOS device driver projects, WORM fundamentals, WORM device driver arquitecture, DOS WORM device driver, A device driver commands, B device driver interface, C arrange utility, D DOS API
Incluye bibliografía
Keywords: DOS - Programas de Sistemas